Large-scale association studies of variants in genes encoding the pancreatic beta-cell K-ATP channel subunits Kir6.2 (KCNJ11) and SUR1 (ABCC8) confirm that the KCNJ11 E23K variant is associated with type 2 diabetes - Gloyn, A; Weedon, M; Owen, K; Turner, M; Knight, B; Hitman, G; Walker, M; Levy, J; Sampson, M; Halford, S; McCarthy, M; Hattersley, A; et al. (2003)
The genes ABCC8 and KCNJ11, which encode the subunits sulfonylurea receptor 1 (SUR1) and inwardly rectifying potassium channel (Kir6.2) of the β-cell ATP-sensitive potassium (KATP) channel, control insulin secretion. Common polymorphisms in these genes (ABCC8 exon 16-3t/c, exon 18 T/C, KCNJ11 E23K) have been variably associated with type 2 diabetes, but no large (∼2,000 subjects) case-control studies have been performed. We evaluated the role of these three variants by studying 2,486 U.K. subjects: 854 with type 2 diabetes, 1,182 population control subjects, and 150 parent-offspring type 2 diabetic trios. The E23K allele was associated with diabetes in the case-control study (odds ratio [OR] 1.18 [95% CI 1.04-1.34], P = 0.01) but did not show familial association with diabetes. Neither the exon 16 nor the exon 18 ABCC8 variants were associated with diabetes (1.04 [0.91-1.18], P = 0.57; 0.93 [0.71-1.23], P = 0.63, respectively). Meta-analysis of all case-control data showed that the E23K allele was associated with type 2 diabetes (K allele OR 1.23 [1.12-1.36], P = 0.000015; KK genotype 1.65 [1.34-2.02], P = 0.000002); but the ABCC8 variants were not associated. Our results confirm that E23K increases risk of type 2 diabetes and show that large-scale association studies are important for the identification of diabetes susceptibility alleles.